Employment Relationship Problem Resolution: a Gap Between Objectives and Implementation - Greenwood, G; Rasmussen, E (ER Publishing Ltd, 2017)
This paper identifies a disjuncture between the policy objectives of the Employment Relations Act 2000 (ERA) and the Employment Relations Problem Resolution system. One objective of the ERA was the early resolution of employment relationship problems close to the workplace. The framing of workplace conflict as Employment Relationship Problems (ERP) heralded a paradigm shift from adversarial escalation of disputes to collaborative problem solving by early negotiation and mediation. Our research suggests that in practice there is a propensity to bypass the intentions of the ERA by confidential settlement negotiation or escalation to a personal grievance; thus, the aim of strengthening employment relationships through processes of early, low-cost, fast and fair conflict resolution by state sponsored institutions appears yet to be fully realised in the education sector. Our research of ERP in the New Zealand education sector indicates the shortfall in meeting the original intentions of the ERA is related to three factors: 1) the complexity of contemporary employment relationships in education; 2) the state provision of processes for early resolution does not include conflict in complex stakeholder relationships; 3) a culture of complaint has a negative impact on trust in school employment relationships. Given that background, this paper sets the scene for the forthcoming publication of a model for collaborative conflict management that provides process guidelines for organisations under the current legislative framework.
Keywords: Employment Relations Act 2000; Employment relationships; Workplace conflict management; Dispute resolution; Education complaints; Conflict resolution; Good faith; Education law